Anophthalmia with cleft palate and micrognathia: a new syndrome? - Phadke, S R (1994)
A 5 day old male with bilateral anophthalmos, hypospadias, bifid scrotum, micrognathia, and cleft palate with normal chromosomes is described. There have been two case reports with similar clinical manifestations but associated with interstitial deletion of 14q (q22q23). We propose that either our patient represents a new syndrome or has a microdeletion which could not be detected on routine cytogenetics. High quality cytogenetics and FISH may show microdeletions in patients presenting with this clinical picture and normal chromosomes.